Aspirin-exacerbated respiratory disease. (October 2020) - Wangberg, Hannah; White, Andrew A
Highlights: AERD patients have baseline sinopulmonary disease worsened upon COX-1 inhibition. Immune dysregulation in AERD involves a highly Type 2 process, impaired PGE2 regulatory processes and elevated CysLTs. Eosinophils, mast cells, ILC2s, and platelet adherent leukocytes contribute to AERD pathogenesis. Aspirin therapy improves clinical and inflammatory markers through several unique mechanisms. Abstract : Aspirin-exacerbated respiratory disease (AERD) classically presents with severe asthma, nasal polyposis, and respiratory exacerbations in response to cyclooxygenase (COX)-1 inhibition. Recent advances in our understanding of AERD have revealed multiple facets of immune dysregulation, including diminished prostaglandin E2 (PGE2 ) function and elevated levels of both cysteinyl leukotrienes (CysLTs) and innate cytokines such as interleukin 33 (IL-33). Inflammatory mediators in AERD heighten the recruitment and activation of innate lymphoid cells type 2 (ILC2), mast cells, eosinophils, and platelet-adherent leukocytes. This contributes to a cyclical pattern of type 2 inflammation. Here, we highlight current understanding of the immunopathogenesis of AERD.